2014
DOI: 10.1371/journal.pone.0100842
|View full text |Cite
|
Sign up to set email alerts
|

The Inferred Cardiogenic Gene Regulatory Network in the Mammalian Heart

Abstract: Cardiac development is a complex, multiscale process encompassing cell fate adoption, differentiation and morphogenesis. To elucidate pathways underlying this process, a recently developed algorithm to reverse engineer gene regulatory networks was applied to time-course microarray data obtained from the developing mouse heart. Approximately 200 genes of interest were input into the algorithm to generate putative network topologies that are capable of explaining the experimental data via model simulation. To cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 84 publications
(99 reference statements)
0
20
0
Order By: Relevance
“…TargetScan works by searching mRNAs sites with high complementarity to the seed region (nucleotides 2-7) of the miRs, assessing sequence features derived from empirically defined rules and site conservation across species. This bioinformatics analysis helps in the interpretation of the biological and molecular role of miRs [22]. TargetScan was specifically used because it is suggested to be one of the most reliable miR target prediction algorithms available, presenting a distinguished tradeoff between sensitivity and specificity [23,24,25].…”
Section: Computational Prediction Of Mir Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…TargetScan works by searching mRNAs sites with high complementarity to the seed region (nucleotides 2-7) of the miRs, assessing sequence features derived from empirically defined rules and site conservation across species. This bioinformatics analysis helps in the interpretation of the biological and molecular role of miRs [22]. TargetScan was specifically used because it is suggested to be one of the most reliable miR target prediction algorithms available, presenting a distinguished tradeoff between sensitivity and specificity [23,24,25].…”
Section: Computational Prediction Of Mir Targetsmentioning
confidence: 99%
“…In general, the use of miR targets prediction softwares that consider site conservation across species, such as TargetScan, is associated with high precision and sensitivity [60]. Comparison between in vivo results and in silico predictions provided by several A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 22 computational methods has revealed that TargetScan is one of the best available algorithms and that the scores associated with predicted interactions correlated with protein downregulation, justifying our choice for this prediction tool [24]. We showed that a high proportion of putative targets found by TargetScan have also support from other computational resources, and that TargetScan presented the most expressive overlap with experimentally validated data among the three in silico methods used (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recon 2 (an improvement over Recon 1) is a model to represent human metabolism and incorporates [139,140] Pathway analysis Breast cancer [141] GoMiner [142] Pathway analysis Pancreatic cancer [143] ClueGo [144] Pathway analysis Colorectal tumors [145] GSEA [146] Pathway analysis Diabetes [147] Pathway-Express [148] P a t h w a y a n a l y s i s L e u k e m i a [ 149] Recon 2 [150] Reconstruction of metabolic networks Drug target prediction studies [151] Boolean methods [135,152,153] Reconstruction of gene regulatory networks Cardiac differentiation [154] ODE models [155][156][157][158] Reconstruction of gene regulatory networks Cardiac development [158] 7,440 reactions involving 5,063 metabolites. Recon 2 has been expanded to account for known drugs for drug target prediction studies [151] and to study off-target effects of drugs [173].…”
Section: Reconstruction Of Regulatory Networkmentioning
confidence: 99%
“…This Boolean model successfully captured the network dynamics for two different immunology microarray datasets. The dynamics of gene regulatory network can be captured using ordinary differential equations (ODEs) [155][156][157][158]. This approach has been applied to determine regulatory network for yeast [155].…”
Section: Reconstruction Of Regulatory Networkmentioning
confidence: 99%
See 1 more Smart Citation